Rosai–Dorfman disease mimicking IgG4-related diseases: a single-center experience in China - Wang, Li; Li, Wei; Zhang, Shangzhu; Peng, Linyi; Shen, Min; Song, Shuoning; Zhang, Wei; Cao, Xinxin; Feng, Ruie; Zhang, Wen (Orphanet journal of rare diseases, 2020)
Rosai-Dorfman disease (RDD) and IgG4-related (IgG4-RD) disease are both rare diseases, but in some cases, RDD mimics IgG4-RD clinically and pathologically. RDD mimicking IgG4-RDs (RDD mimic IgG4-RD), referring to disease initially diagnosed as IgG4-RD but finally pathologically confirmed to be RDD, is a clinically rare and confusing disease. To summarize the characteristics of this disease, we prospectively analyzed the clinical features, laboratory parameters, pathological characteristics, treatment and prognosis of patients diagnosed with RDD mimic IgG4-RD. Moreover, by analyzing characteristics of RDD mimic IgG4-RD, RDD and IgG4-RD, we further compared the similarities and differences between RDD and IgG4-RD. 7 patients with RDD mimic IgG4-RD were included in this study and all of them had extranodal organ involvement, especially the central nervous system, which occurred in 5 patients (71.4%). Although serum IgG4 level was elevated in 6 cases (1360-54,100 mg/L), overall, it was still lower than that in IgG4-RD patients. Furthermore, we found a new cut-off value of serum IgG4 concentration for differentiating RDD and IgG4-RD with higher specificity. Pathological findings of RDD also showed features resembling IgG4-RD: IgG4-positive plasma cell enrichments were observed in all RDD mimic IgG4-RD patients, and the proportion of IgG4/IgG in tissues was 10-40% in 4 patients and more than 40% in 2 patients. However, none of the RDD mimic IgG4-RD patients or RDD patients displayed obliterative phlebitis or storiform fibrosis. Most of the RDD mimic IgG4-RD patients were treated with glucocorticoids combined with immunosuppressants, and a good prognosis was obtained following treatment. RDD has clinical manifestations that mimic IgG4-RD. However, detailed differences in laboratory parameters and pathological characteristics are present between these two diseases. Our study underlines the necessity to rule out RDD while diagnosing IgG4-RD using pathological findings as the identification criteria and provides advice for both differentiating these two diseases and clinical treatment of RDD mimic IgG4-RD.